(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article represents the humanity concept in the poetic works of Lina Kostenko. The term “humanity concept” is determined as a special internal organization and complex structure which is formed by a set of the corresponding notions and lexical meanings of the word “humanity”. Among these definitions can be distinguished the following: a) all people of the Earth, mankind, human society; b) people who live now and become the contemporaries to a certain person or some significant event; c) a large number of people united by certain positive traits. The paper points at the fact that in terms of a certain context the analyzed language unit modifies its semantics in different ways. Humanity is perceived not only as a set of people consisting of individuals, but also it is supposed to be as a certain human community which has played a leading role in the cultural and historical processes. This article reveals the idea that within the poetic works of L. Kostenko the humanity concept is represented mainly through the prism of the people notion which is marked with multiple forms of expression and comes into synonymic relations with a colloquial word people. Lingual interpretation of the humanity concept is investigated through the prism of the person concept expressed by the word person.